The Small Mammals of the Mackenzie Delta Region, Northwest Territories, Canada - Martell, Arthur M.; Pearson, Arthur M. (ARCTIC, 1978)
The paper reports on 3800 small mammals taken in taiga and tundra east of the Mackenzie River Delta between 1971 and 1974. Local distributions are given for all 100 species of small mammals recorded in the region, plus two accidentals. In addition, abundance, body and cranial measurements, and reproductive information is presented for the 8 species collected during the study. The taxonomic status of Clethrionomys rutilus platycephalus is discussed.